Briefe I (1884-1894) - Graf, Friedrich Wilhelm (Ernst Troeltsch: Kritische Gesamtausgabe, 2013)
The first volume of letters in the Troeltsch Complete Critical Edition includes the letters written by the young Ernst Troeltsch between 1884 and 1894, along with several letters addressed to him. These 102 letters, most of them previously unknown, provide fascinating insights into the process of Troeltsch's theological education and his spiritual turmoil as he searched for a truly independent intellectual position amidst the competing worldviews swirling around him in the German Empire. These letters reveal the great importance of the debates that took place in the Uttenruthia Student Associa